Resistive index of retinal arterial blood flow in type-II diabetics without retinopathy (Bangladesh Medical Journal Khulna, 2015)
Diabetic retinopathy is a vascular disorder affecting the microvasculature of retina. It is caused by changes in the blood vessels of retina. If untreated, it may lead to blindness. Therefore if diagnosed and treated promptly, blindness is usually preventable. In ophthalmology, Colour Doppler Imaging is a new method that enables us to assess the orbital vasculature. Duplex color Doppler ultrasonography is the investigation of choice to assess retinal arterial flow velocities very quickly without any invasive procedure for qualitative and quantitative assessment of blood flow velocities. This study was performed to observe the difference between Doppler flow velocity indices of retinal artery in Type-II Diabetics subjects without retinopathy and those of normal control subjects. This case-control study was carried out in the Radiology department, BIRDEM for two years. All the selected subjects underwent Duplex Doppler ultrasonography of both eyes using 5 to 7.5 MHz linear phase transducer. Findings included spectral analysis, those were PSV, EDV and RI. Unpaired ttest was done to compare blood flow velocity indices of retinal artery in type-II diabetic patients without retinopathy and that of healthy control adult subjects and a P value